Influence of resisted sled‐push training on the sprint force‐velocity profile of male high school athletes. (5th December 2019) - Cahill, Micheál J.; Oliver, Jon L.; Cronin, John B.; Clark, Kenneth P.; Cross, Matt R.; Lloyd, Rhodri S.
Abstract : Sled pushing is a commonly used form of resisted sprint training; however, little empirical evidence exists, especially in youth populations. The aim of this study was to assess the effectiveness of unresisted and resisted sled pushing across multiple loads. Fifty high school athletes were assigned to an unresisted (n = 12), or 3 resisted groups; light (n = 14), moderate (n = 13), and heavy (n = 11) resistance that caused a 25%, 50%, and 75% velocity decrement in maximum sprint speed, respectively. All participants performed two sled‐push training sessions twice weekly for 8 weeks. Before and after the training intervention, the participants performed a series of jump, strength, and sprint testing to assess athletic performance. Split times between 5 and 20 m improved significantly across all resisted groups (all P < .05, d = 0.34‐1.16) but did not improve significantly with unresisted sprinting. For all resisted groups, gains were greatest over the first 5 m ( d = 0.67‐0.84) and then diminished over each subsequent 5 m split ( d = 0.08‐0.57). The magnitude of gains in split times was greatest within the heavy group. Small but non‐significant within‐group effects were found in pre to post force‐velocity profiles. There was a main effect of time but no interaction effects as all groups increased force and power, although the greatest increases were observed with the heavy load ( d = 0.50‐0.51). The results of this study suggest that resisted sled pushing with any load was superior to unresisted sprint training and that heavy loads may elicit the greatest gains in sprint performance over short distances.